A comparison of sexual desire in opiate-dependent men receiving methadone and buprenorphine maintenance treatment - Yee, Anne; Loh, Huai Seng; Loh, Huai Heng; Riahi, Shahrzad; Ng, Chong Guan; Sulaiman, Ahmad Hatim (BMC, 2019)
Background: Methadone is an effective therapy for opiate dependence. However, one of the commonest side effects is sexual dysfunction among male patients. Buprenorphine is an alternative to methadone. This study aimed to compare sexual desire among opiate-dependent male patients on buprenorphine (BMT) and methadone maintenance therapy (MMT). Methods: This cross-sectional study involved 126 male opiate-dependent patient who were tested for total testosterone (TT) and prolactin levels, and were interviewed and completed the Sexual Desire Inventory-2 (SDI-2), Malay language of International Index of Erectile Function (Mal-IIEF-15) and the Malay version of the self-rated Montgomery-Asberg Depression Rating Scale (MADRS-BM) questionnaires. Results: There were 95 (75.4%) patients on MMT and 31 (24.6%) on BMT. Patients on MMT scored significantly lower in the sexual desire domain (Mal-IIEF-15 scores) (p < 0.01), dyadic sexual desire (p = 0.04) and TT plasma level (p < 0.01) when compared to BMT group after controlling all the confounders. Conclusions: Patients on MMT are associated with lower sexual desire when compared with patients on BMT. Smoking may further lower testosterone and, hence, sexual desire in those already on methadone. © 2019 The Author(s).